2017
DOI: 10.1111/nyas.13378
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the paracellular channels formed by claudins of the blood–brain barrier tight junctions

Abstract: Tight junctions (TJs) are key players in determining tissue-specific paracellular permeability across epithelial and endothelial membranes. Claudin proteins, the primary determinants of TJs structure and functionality, assemble in paracellular spaces to form channels and pores that are charge and size selective. Here, using molecular dynamics (MD) simulations, we elucidate the molecular assembly of claudin-3 and claudin-5 proteins of blood-brain barrier TJs. Despite having a high degree of sequence and structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
123
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(139 citation statements)
references
References 67 publications
(189 reference statements)
16
123
0
Order By: Relevance
“…Strikingly, the loop region between β 1 and β 2 (residues 34 to 41) is missing in the crystal structure. The monomeric structure of Cldn15 has been employed in coarse-grained computational studies [ 23 ], and as a template to build structural models of several other claudins [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, the loop region between β 1 and β 2 (residues 34 to 41) is missing in the crystal structure. The monomeric structure of Cldn15 has been employed in coarse-grained computational studies [ 23 ], and as a template to build structural models of several other claudins [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly however, computational studies based on coarse-grained models [ 24 ] demonstrated that for a different claudin (Cldn5), whose structure was modeled by homology with Cldn15, a cis arrangement similar to that of Suzuki et al is among those that are spontaneously formed by monomers. Morover, by docking these Cldn5 dimers [ 25 ], it was possible to reconstruct a single-pore structure similar to the Cldn15 model of Suzuki et al…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this model is not compatible with studies suggesting the role of TM helices in claudin assembly and strand formation through cis-interactions [37][38][39][40][41]. Based on these interactions, alternative pore models have been proposed [37,42,43]. With recent advances in computational techniques, molecular dynamics simulations can reach time scales and sizes relevant to study assembly and initial stages of protein aggregation [44][45][46][47][48][49] and can provide an insight into alternative conformations of claudins in the TJ strands.…”
Section: Ion Transport Simulationsmentioning
confidence: 91%
“…For example, there are significant differences in how claudin-5 and claudin-3 oligomerize and this is thought to be due to differences in key residues in TM3 [39]. To investigate the role of TM3 helices in the self-assembly of claudins in the membrane, Irudayanathan et al [43] simulated the assembly of homology models of claudin-3 and claudin-5 in lipid bilayers at CG resolution. The self-assembly trajectory of claudin-3 monomers showed that the dimer with TM2-TM3 interface, detected in claudin-5 trajectories, was absent in claudin-3, while other dimer interfaces were detected.…”
Section: Claudin Polymerization In Lipid Bilayersmentioning
confidence: 99%
See 1 more Smart Citation